NON-LTE EFFECTS IN ALI LINES: CHOICE OF ATOMIC DATA - Menzhevitski, V. V.; Shimanskaya, N. N.; Shimansky, V. V.; Kudryavtsev, D. O.; Sakhibullin, N. A. (Одеські астрономічні публікації, 2013)
We performed special test calculations for 2 diﬀerent sets of atomic data: with data from TOP base database (Seaton M.J.,Zeippen C.J.,Tully .A. et al., 1992), and with set of sections from (Hofsaess D., 1979) to estimate the eﬀect of adopted values of photo ionization cross-sections on the value of non-LTE deviations.